ضمان جودة التعليم العالي في سورية ومواءمته مع احتياجات مجتمع المستفيدين في ضوء المعايير المرجعية الأكاديمية الوطنية (NARS) (دراسة حالة برنامج المصارف والتمويل في كلية الاقتصاد بجامعة تشرين) - طرابلسية, شيراز (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تشهد منظومة التعليم العالي في سورية نموﴽ مطردﴽ وفقاﹰ لمؤشرات عديدة في مقدمتها ازدياد الطلب على التعليم العالي كماﹰ نتيجة للزيادة السكانية والإقبال الاجتماعي المتزايد على التعليم، ونوعاﹰﹰﹰ نتيجة للحاجة المتزايدة إلى مواكبة حركة النمو العالمية التي تجتاح المجتمعات كافة، في المجالات العلمية والثقافية والاقتصادية والاجتماعية.بناءﹰ على ذلك هدف البحث إلى التحقق من جودة مخرجات التعليم العالي في البرامج التعليمية لكلية الاقتصاد في جامعة تشرين في إطار المعايير المرجعية الأكاديمية الوطنية (NARS) المتعلقة بالمعارف والفهم والمهارات المهنية والعملية، وذلك لضمان مواءمتها مع احتياجات مجتمع المستفيدين منها.وقد دلت النتائج على وجود فروق ذات دلالة فيما يتعلق بمهارات المعرفة والفهم، والمهارات المهنية والعملية، لخريجي برنامج المصارف والتمويل، وبين المهارات التي يحتاجها أرباب العمل.The System of Higher Education in Syria witnesses a constant development according to numerous indictors ahead of which is the increased demand towards higher education quantitatively in result of population increase and the increasing social interest in learning, and qualitatively due to the increasing need for keeping pace with the international growth process that invades all the societies in the scientific, cultural, economical and social domains. Accordingly, this research aimed at the affirmation of the higher education output quality in the curriculums of Faculty of Economy in Tishreen University within the framework of the National Academy Reference Standards (NARS) related to the professional and practical knowledge, understanding and skills, in a way that assures its convenience with the needs of beneficiaries community thereof. The results have shown the existence of indicative differences between the professional and practical knowledge, understanding and skills acquired by the graduates of Banking and Financing Program and those skills needed by Employers.